2014
DOI: 10.1186/s12931-014-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Small airway dysfunction is associated to excessive bronchoconstriction in asthmatic patients

Abstract: BackgroundWe investigated whether a relationship between small airways dysfunction and bronchial hyperresponsiveness (BHR), expressed both in terms of ease of airway narrowing and of excessive bronchoconstriction, could be demonstrated in asthma.Methods63 (36 F; mean age 42 yr ± 14) stable, mild-to-moderate asthmatic patients (FEV1 92% pred ±14; FEV1/FVC 75% ± 8) underwent the methacholine challenge test (MCT). The degree of BHR was expressed as PD20 (in μg) and as ∆FVC%. Peripheral airway resistance was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…12,13 In line with previous studies, 12 the authors found significant effects on small airway measurements (R5eR20) during standardized bronchial challenge testing. Small airway dysfunction within asthma is becoming recognized as a distinct clinical phenotype associated with poor asthma control.…”
Section: Discussionsupporting
confidence: 86%
“…12,13 In line with previous studies, 12 the authors found significant effects on small airway measurements (R5eR20) during standardized bronchial challenge testing. Small airway dysfunction within asthma is becoming recognized as a distinct clinical phenotype associated with poor asthma control.…”
Section: Discussionsupporting
confidence: 86%
“…Small airways disease, assessed by peripheral airway resistance, has recently been associated with excessive bronchoconstriction in asthmatic patients [42]. Our data support the role of FEF 25-75% as a marker of early airway obstruction and as a risk factor for BHR positivity and severity in agreement with previous reports on allergic [43,44,45] and rhinitic subjects [10]; therefore, in clinical practice a more rational approach should also include measurements of FEF 25-75% [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ΔFVC% correlated to asthma treatment in adult patients and to the presence of symptoms in children with asthma [98, 99]. Recently, Alfieri et al provide the first evidence that in asthmatic patients excessive bronchoconstriction expressed by ΔFVC% is strictly associated to small airway dysfunction, as assessed by IOS [100]. As compared to patients with R5–R20 ≤ 0.030 kPa s l −1 , patients with R5–R20 > 0.030 kPa s l −1 had a high likelihood to be associated to a ΔFVC% greater than 14.5 % during a methacholine-induced bronchoconstriction.…”
Section: Introductionmentioning
confidence: 99%